NILS ANFINSET, Metal, Nomads and Culture Contact. The Middle East and North Africa. London, Equinox, 2010, 241 pp., with illustrations, maps and photographs. ISBN 978-1-84553-253-6. U$D 96.00 - Quintana, Carolina (2010)
Fil: Quintana, Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina